Properties and inhibition of the first two enzymes of the non-mevalonate pathway of isoprenoid biosynthesis. (December 2000) - Mueller, C.; Schwender, J.; Zeidler, J.; Lichtenthaler, H. K.
Abstract : Enzymes of the 1-deoxy-D-xylulose 5-phosphate/2- C -methylerythritol 4-phosphate (DOXP/MEP) pathway are targets for new herbicides and antibacterial drugs. Until now, no inhibitors for the DOXP synthase have been known of. We show that one of the breakdown products of the herbicide clomazone affects the DOXP synthase. One inhibitor of the non-mevalonate pathway, fosmidomycin, blocks the DOXP reductoisomerase (DXR) of plants and bacteria. The I50 values of plants are, however, higher than those found for the DXR of Escherichia coli. The DXR of plants, isolated from barley seedlings, shows a pH optimum of 8.1, which is typical for enzymes active in the chloroplast stroma.